Problems of Implementing the Death Penalty in the Context of Law Enforcement in Indonesia (Analysis of the Sambo Case) - Made Feri; A.A Sagung Poetri Praniti; Ida Bagus Anggapurana Pidada (PT FORMOSA CENDEKIA GLOBAL, 2023)
The death penalty is a punishment that is still recognized as being implemented in Indonesia. The death penalty is usually applied to perpetrators of certain crimes where the crime falls into the category of extraordinary crimes. This research was conducted using the normative legal research method (normative law research) using normative case studies in the form of legal behavior products. Legal certainty regarding the death penalty can be seen in Article 10 letter a of the Criminal Code (KUHP), explaining that the death penalty is one of the basic punishments. At the same time, article 28A of the 1945 Constitution explains that